2017
DOI: 10.1111/ijac.12848
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, thermoelectrical, and magnetic study of Zn1‐xCoxO (0 ≤ x ≤ 0.10) nanocrystals

Abstract: In this work, we have prepared Co‐doped ZnO nanocomposites by zinc nitrate and cobalt sulfate as new precursors via the coprecipitation method and the samples were followed to identify the morphological, optical, structural, and magnetic properties. The XRD patterns revealed the crystalline nature of nanoparticles with hexagonal wurtzite structures, which meant that Co impurity did not disturb the structure of pure ZnO and the minimum crystallite size of nanoparticles was calculated to be around 37 nm. The XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…In the region ranging from 500 to 750 nm we can clearly observe a decrease in the average transmittance from 84 to 57 % with the increase of cobalt concentration. The observed spectra were very similar to those obtained in the literature for Co doped ZnO thin films [21][22][23][24][25]. Due to the similar ionic radii of Zn +2 (0.60 Å) and…”
Section: Micro Raman Spectroscopysupporting
confidence: 87%
“…In the region ranging from 500 to 750 nm we can clearly observe a decrease in the average transmittance from 84 to 57 % with the increase of cobalt concentration. The observed spectra were very similar to those obtained in the literature for Co doped ZnO thin films [21][22][23][24][25]. Due to the similar ionic radii of Zn +2 (0.60 Å) and…”
Section: Micro Raman Spectroscopysupporting
confidence: 87%
“…A sructural study done by Akhtari et al 153 has shown a decrease in lattice parameters a and c with concentration (Figure 14). Co plays an important role in optoelectronic properties such as the dielectric constant, refractive index, absorption coefficient, relative transmittance and absorbance, and extinction coefficient.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 92%
“…The room temperature susceptibility was found to be in the range of 10 −4 emu g −1 when measured in a field of 1000 Oe for Co-doped ZnO, while for Mn-doped ZnO it comes in the range of only 10 −6 emug −1 . 153 The Cr-, Mn-, and Ni-doped nc-ZnO films show the well-defined ferromagnetic features at RT. The coercivity is 34, 56, and 54 Oe for ZnO:Cr, ZnO:Mn, and ZnO:Ni film, respectively.…”
Section: Properties Of Tm Znomentioning
confidence: 95%
See 1 more Smart Citation
“…Metal oxide semiconductors are widely used because of their excellent properties and numerous applications in optical and electronic fields . Aluminum oxide (Al 2 O 3 ) is an electric insulator with relatively high heat conductivity.…”
Section: Introductionmentioning
confidence: 99%